Hormonal stress responses of growth hormone and insulin-like growth factor-I in highly resistance trained women and men. (August 2021) - Hatfield, Disa L.; Kraemer, William J.; Volek, Jeff S.; Nindl, Bradley C.; Caldwell, Lydia K.; Vingren, Jakob L.; Newton, Robert U.; Häkkinen, Keijo; Lee, Elaine C.; Maresh, Carl M.; Hymer, Wesley C.
Abstract: The purpose of this study was to examine the responses of growth hormone (GH) and insulin-like growth factor-I (IGFI) to intense heavy resistance exercise in highly trained men and women to determine what sex-dependent responses may exist. Subjects were highly resistance trained men ( N  = 8, Mean ± SD; age, yrs., 21 ± 1, height, cm, 175.3 ± 6.7, body mass, kg, 87.0 ± 18.5, % body fat, 15.2 ± 5.4, squat X body mass, 2.1 ± 0.4; and women ( N  = 7; Mean ± SD, age, yrs. 24 ± 5, height, cm 164.6 ± 6.7, body mass, kg 76.4 ± 8.8, % body fat, 26.9 ± 5.3, squat X body mass, 1.7 ± 0.6). An acute resistance exercise test protocol (ARET) consisted of 6 sets of 10 repetitions at 80% of the 1 RM with 2 min rest between sets was used as the stressor. Blood samples were obtained pre-exercise, after 3 sets, and then immediately after exercise (IP), 5, 15, 30, and 70 min post-exercise for determination of blood lactate (HLa), and plasma glucose, insulin, cortisol, and GH. Determination of plasma concentrations of IGFI, IGF binding proteins 1, 2, and 3 along with molecular weight isoform factions were determined at pre, IP and 70 min. GH significantly ( P  ≤ 0.05) increased at all time points with resting concentrations significantly higher in women. Significant increases were observed for HLa, glucose, insulin, and cortisol with exercise and into recovery with no sex-dependent observations. Women showed IGF-I values that were higher than men at all times points with both seeing exercise increases. IGFBP-1 and 2 showed increase with exercise with no sex-dependent differences. IGFBP-3 concentrations were higher in women at all-time points with no exercise induced changes. Both women and men saw an exercise induced increase with significantly higher values in GH in only the mid-range (30-60 kD) isoform.  Only women saw an exercise induced increase with significantly higher values for IGF fractions only in the mid-range (30–60 kD) isoform, which were significantly greater than the men at the IP and 70 min post-exercise time points. In conclusion, the salient findings of this investigation were that in highly resistance trained men and women, sexual dimorphisms exist but appear different from our prior work in untrained men and women and appear to support a sexual dimorphism related to compensatory aspects in women for anabolic mediating mechanisms in cellular interactions. Highlights: Women differentiated their responses from men with higher concentrations of GH at rest and in mid-range fraction of GH Women showed higher IGF-I concentrations at rest and recovery with a differential mid-range molecular weight fraction. Plasma levels of growth hormone dimers are significantly higher in blood after exercise. While sexual dimorphisms exist, they are different s than previously observed in untrained men and women.